2020
DOI: 10.4025/actascibiolsci.v42i1.52940
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagation and in vitro conservation of Alcantarea nahoumii (Bromeliaceae), an endemic and endangered species of the Brazilian Atlantic Forest

Abstract: Alcantarea nahoumii (Leme) J. R. Grant is a species native to the Atlantic Forest that stands out for ornamental purposes. The objective of this work was to evaluate the in vitro germination of A. nahoumii seeds and establish a micropropagation protocol for production of seedlings so as to minimize the effects of predatory extractivism and develop an in vitro conservation system. Mature seeds were disinfested, established in three culture media (MS, MS½ and MS⅓) and incubated at four temperatures (20, 25, 30 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…The results observed for the number and length of leaves or roots and the biomass accumulation confirmed that the increased BAP concentration favored A. setigera multiplication rather than the growth of plant organs. Similar results with the use of BAP and ANA were obtained with bromeliad Alcantarea nahoumii (Silva et al, 2020), indicating that the use of this cytokinin in higher concentrations increases the multiplication rate, an important characteristic for the propagation and conservation of the species.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…The results observed for the number and length of leaves or roots and the biomass accumulation confirmed that the increased BAP concentration favored A. setigera multiplication rather than the growth of plant organs. Similar results with the use of BAP and ANA were obtained with bromeliad Alcantarea nahoumii (Silva et al, 2020), indicating that the use of this cytokinin in higher concentrations increases the multiplication rate, an important characteristic for the propagation and conservation of the species.…”
Section: Discussionsupporting
confidence: 71%
“…The in vitro propagation system of bromeliads of Aechmea genera performed from shoots presented viability and can be used as a biotechnology strategy for the conservation of bromeliads, minimizing the extractive activity, as suggested by other authors (Santa- Rosa et al, 2013;Leão et al, 2014, Silva et al, 2020. This system can also be used for clonal propagation of plants with ornamental potential (Guerra and Dal Vesco, 2010;Faria et al, 2018).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Among the most popular culture media, the MS medium (Murashige and Skoog, 1962) is widespread in tissue culture research and has been used in in vitro culture of many species in specific concentrations for each of them. In a study developed by Silva et al (2020) with Alcantarea nahoumii (Bromeliaceae), for example, plants grown in MS medium with half the salt concentration had the lowest growth. According to the authors, this fact indicates a metabolism reduction useful for in vitro conservation.…”
Section: Introductionmentioning
confidence: 99%